Reflection of Strategic Thinking in Activating Organizational Conflict Management Strategies (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This research aims to determine the nature of the role of strategic thinking and its impact in improving organizational conflict management strategies in business organizations. Strategic thinking is the key driver of all changes that the organization can make to adapt to the environment in which it operates. Improving organizational conflict management strategies is one of the challenges Which face the top management of the contemporary organization to help them survive. The research problem indicated that there is a clear lack of strategic thinking in improving organizational conflict management strategies. The General Company for Vegetable Oils was chosen as the field of application. The sample was selected in a simple random sample of 104 persons. The questionnaire was adopted as a tool for obtaining On the data of the research, which was prepared based on a number of ready-made measurements after being subjected to tests of honesty and consistency. The statistical tools resulted in a number of results, most of which confirmed the existence of a relationship of correlation and effect of significance to strategic thinking in the sense of Organizational Conflict Management Strategies therefore been accepted and the main sub-hypotheses contained in the research.